2019
DOI: 10.4236/ajcm.2019.93012
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of the Transmission Dynamics of Tuberculosis

Abstract: We develop a dynamical model to understand the underlying dynamics of TUBERCULOSIS infection at population level. The model, which integrates the treatment of individuals, the infections of latent and recovery individuals, is rigorously analyzed to acquire insight into its dynamical features. The phenomenon resulted due to the exogenous infection of TUBERCULOSIS disease. The mathematical analysis reveals that the model exhibits a backward bifurcation when TB treatment remains of infected class. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…To integrate (21), refs. [23,33] have applied two-step Lagrange interpolation to solve this integration, and we use similar knowledge to write our proposed model (1) in the following form as [20]:…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…To integrate (21), refs. [23,33] have applied two-step Lagrange interpolation to solve this integration, and we use similar knowledge to write our proposed model (1) in the following form as [20]:…”
Section: Numerical Simulationmentioning
confidence: 99%
“…MDR-TB treatment and prevention have become increasingly important in recent years, and they comprise the focus of this article [18] . Other articles that deal with the modelling of TB can be found in [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Te use of mathematical models to capture the causes and the control of infectious diseases has been studied widely [10][11][12][13]. Mathematical deterministic models have considerably been applied to comprehend the behaviour of infections both at population and within host levels including proposing strategic intervention approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Nayeem and Sultana (2019) developed a dynamical model to understand the underlying dynamics of Tuberculosis infection at the population level by incorporating treatment of individuals, the infection of latent and recovery individuals. Their analysis revealed that the model exhibits a backward bifurcation when TB treatment remains in the infected class.…”
mentioning
confidence: 99%